Molecular data provide new insights into the phylogeny of Cladonotinae (Orthoptera: Tetrigoidea) from China with the description of a new genus and species - Zhang, Rong-Jiao; Zhao, Cong-Lin; Wu, Fei-Peng; Deng, Wei-An (Zootaxa, 2020)
Considerable effort has been devoted to elucidating the phylogenetic relationships of tetrigides. However, there is still no commonly accepted phylogenetic hypothesis. Therefore, the phylogenetic relationships among some subfamilies remain unclear; e.g., Cladonotinae is a controversial group, in which the phylogenetic relationships between genera and the boundaries of some of the included genera are unclear, causing some of the taxa to be difficult to identify. Therefore, an in-depth phylogenetic analysis of Cladonotinae is urgently needed. In this study, a robust phylogenetic framework for the tetrigides was reconstructed based on the combined mitochondrial cytochrome oxidase subunit I (COI), 16S ribosomal RNA (16S rRNA), and nuclear 18S ribosomal RNA (18S rRNA) gene sequences of 25 species belonging to 16 genera of Tetrigoidea from China, which included 13 species from 8 genera of Cladonotinae. Phylogenetic inferences were performed using the combined dataset and Bayesian inference (BI) and Maximum Parsimony (MP) methods, and the phylogenetic tree of Cladonotinae was reconstructed. All inferences based on the results of the present study supported the Cladonotinae subfamily as a polyphyletic group; within the Cladonotinae subfamily, Tetradinodula, and Tuberfemurus were closely related to Tetriginae, while Austrohancockia and Gibbotettix showed a close relationship to the Scelimenidae subfamily. Additionally, a new genus and new species of the Cladonotinae subfamily are described and illustrated: Hainantettix Deng, gen. nov. and Hainantettix strictivertex Deng, sp. nov.